(untitled) (Journal of Contemporary Philology, 2022)
This paper explores some aspects of the Anglo-centred (US-based and UK-based educational practices) academic literacy promoted in a non-native English academic context. It seeks to understand better how mentors who were trained and partly educated in an Anglo-centred settings, or never received education abroad, affect the bachelor thesis writing process of their mentees. Through several methods such as analysis of theses’ structures written in L2 (English), surveys and semi-structured interviews with students and with their mentors in three fields, I will present the findings on how the student positioning is affected when they write a BA thesis in English, while simultaneously trying to cope with the transcultural instruction and the local institutional requirements. The thematic analysis also highlights a range of educational practices and understandings of the thesis writing process including, on one hand, how students build argumentation, distinguish between facts and opinions, become objective, avoid plagiarism following the Anglo-centred writing instruction and, on the other, a fluidity in how university professors use their diverse linguistic and educational resources for the same purpose, without challenging the dominating values of the L2 academic literacy.